2017
DOI: 10.2147/dddt.s133944
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the human Na<sub>v</sub>1.5 sodium channel: structural and mechanistic insights of ion permeation and drug blockade

Abstract: Abnormalities in the human Nav1.5 (hNav1.5) voltage-gated sodium ion channel (VGSC) are associated with a wide range of cardiac problems and diseases in humans. Current structural models of hNav1.5 are still far from complete and, consequently, their ability to study atomistic interactions of this channel is very limited. Here, we report a comprehensive atomistic model of the hNav1.5 ion channel, constructed using homology modeling technique and refined through long molecular dynamics simulations (680 ns) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 85 publications
3
31
0
Order By: Relevance
“…Several recent MD studies used eukaryotic Na V homology models (Mahdavi & Kuyucak, ; Ahmed et al . ), hybrid models with a grafted SF eukaryotic Na V channel SF onto bacterial structures (Li et al . ; Flood et al .…”
Section: Ion Conductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent MD studies used eukaryotic Na V homology models (Mahdavi & Kuyucak, ; Ahmed et al . ), hybrid models with a grafted SF eukaryotic Na V channel SF onto bacterial structures (Li et al . ; Flood et al .…”
Section: Ion Conductionmentioning
confidence: 99%
“…Their SFs display asymmetries with aspartic acid, glutamic acid, lysine and alanine (DEKA) from different channel domains forming Na + binding site Site HFS compared to the EEEE ring in prokaryotic channels. Several recent MD studies used eukaryotic Na V homology models (Mahdavi & Kuyucak, 2015;Ahmed et al 2017), hybrid models with a grafted SF eukaryotic Na V channel SF onto bacterial structures (Li et al 2017b;Flood et al 2018) as well as new Na V PaS structure . These studies identified a unique asymmetric Na + permeation pathway involving coordination with Asp and Glu residues in the DEKA ring as well as in the outer SF.…”
Section: Ion Movement Across K + Channel Selectivity Filtermentioning
confidence: 99%
“…The first pioneering MD simulation with the peptide neurotoxin I (SH1) from the sea anemone Stichodactyla helianthus was conducted in 1991 [ 163 ]. A later important step in MD application to Na V channel research was the generation of homology model simulations of the Na V channel recognition properties towards the tarantula peptide toxin psalmotoxin-1 [ 164 ], which can bind to a particular isoform (ASIC1) of the Acid Sensing Ion Channel. Although ASICs are proton-gated Na + channels and open when H + binds, unlike the Na V channels involved in recognition of guanidinium toxins, the general MD modelling approach should be applicable for these non-peptidic toxins.…”
Section: Guanidinium Toxins As Ion Channel Research Subjects and Tmentioning
confidence: 99%
“…Nevertheless, sophisticated methods and high-performance computing would be needed for modeling the multi-domain architecture of the human CaVs. Building these models can be helpful in understanding the structure-function-dynamic properties, the Ca 2+ influx mechanisms and effects of small molecules on these channels [48,49].…”
Section: Ion Channels In Health and Sicknessmentioning
confidence: 99%